Role of the Thrombelastograph as an adjunctive test in thrombophilia screening. - O'Donnell, J; Riddell, A; Owens, D; Handa, A; Pasi, J; Hamilton, G; Perry, D (2004)
The Thrombelastograph (TEG) provides a global assessment of haemostatic function. We have investigated the potential role of TEG in thrombophilia testing by studying 87 consecutive patients (all with personal or family history of thrombosis). For each patient, routine thrombophilia screening tests and TEG were performed in parallel. In keeping with previous reports, at least one thrombophilic trait was identified in 34% of the patients. Among those patients with previous thrombosis, the yield from screening was higher (54% with prothrombotic trait). Overall, a hypercoaguable TEG was demonstrated in 45% of patients. However, TEG and standard thrombophilia testing did not necessarily identify the same subset of individuals. Of 39 patients with hypercoaguable TEG, only 17 had a demonstrable thrombophilic trait. Conversely, of 30 patients with proven thrombophilia, 17 also had a hypercoaguable TEG. We conclude that TEG cannot be used as a sole initial screening test in patients referred for thrombophilia testing, as it fails to identify 43% of underlying thrombophilic traits. However, TEG may be a useful adjunctive test, particularly in patients in whom the regular thrombophilia screen proves unremarkable. Prospective studies are warranted to determine whether a hypercoaguable TEG can be used to predict a subset of patients at increased risk for recurrent thrombotic events.